2013
DOI: 10.1007/s40264-013-0114-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Severity of Adverse Drug Reactions Due to Self-Medication: A Cross-Sectional Multicentre Survey in Emergency Departments

Abstract: Background Little is known about the relation of adverse drug reactions (ADRs) to self-use of medications. Objective The aim of this study was to determine the frequency and severity of ADRs related to self-medication (ADR-SM) among emergency department (ED) patients and to describe their main characteristics. Methods A prospective, cross-sectional, observational study was conducted over a period of 8 weeks (1 March to 20 April 2010), in the ED of 11 French academic hospitals. Adult patients presenting to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 19 publications
4
56
1
3
Order By: Relevance
“…A study cites that 1.72% out of 9.78% of ADRs related admissions to emergency wards of 11 French academic hospitals were due to self-medication. 9 These ADRs were caused due to both prescription and non-prescription drugs.…”
Section: Introductionmentioning
confidence: 99%
“…A study cites that 1.72% out of 9.78% of ADRs related admissions to emergency wards of 11 French academic hospitals were due to self-medication. 9 These ADRs were caused due to both prescription and non-prescription drugs.…”
Section: Introductionmentioning
confidence: 99%
“…While an appropriate self-administration of these remedies can provide some benefit (e.g., patient empowerment, reduction of health expenditure by government) [3], a non-responsible use can lead to serious health hazards [6, 8] (e.g., misuse, wrong dosage, adverse health events or interactions). The results of three recent studies [46] demonstrated that self-administration of substances is more prevalent among women probably because they seem more willing than men to recognize and voice the symptoms of health ailments [7].…”
Section: Introductionmentioning
confidence: 99%
“…Unjustified and inappropriate self-medication results in wastage of healthcare resources and increases resistance of pathogens, drug-drug interactions, and adverse drug reactions leading to hospital admissions [12,13,14,15]. Most of the studies on self-medication in children have investigated the use of medicines by children themselves [16,17].…”
Section: Discussion:-mentioning
confidence: 99%
“…This practice is widespread around the world (1) .The practice of self-medication among children consider really important since they constitute a large percentage of the population in developing countries and are prone to many illnesses (2) . Unjustified and inappropriate self-medication results in wastage of healthcare resources and increases resistance of pathogens, drugdrug interactions, and adverse drug reactions leading to hospital admissions (3)(4)(5)(6). Younger children are often given medications by their parents because the first response by most families to many illnesses in their children has been found to be the use of non-prescribed drugs.…”
mentioning
confidence: 99%